Nexrutine and exercise similarly prevent high grade prostate tumors in transgenic mouse model. - Darpan I Patel; Kira Abuchowski; Roble Bedolla; Paul Rivas; Nicolas Musi; Robert Reddick; A Pratap Kumar (PLoS ONE, 2019)
The purpose of this investigation was to compare the antitumorigenic effects of the natural product Nexrutine to voluntary wheel running (VWR) in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model. Forty-five, 10-week old TRAMP mice were randomized to either receive free access to the running wheel, Nexrutine pelleted into chow at 600 mg/kg or no treatment control. Mice were serially sacrificed at weeks 4, 8,12 and 20 weeks. Palpable tumors, body weight, food consumption and running wheel activity were monitored weekly. At necropsy, tumors and serum were harvested and stored for analysis. Serum was used to quantify circulating cytokines in 4 and 20 week time points. Nexrutine supplementation led to a 66% protection against high grade tumors. Exercise resulted in a 60% protection against high grade tumors. Both interventions reduced concentrations of IL-1α. Exercise also significantly lowered concentrations of eotaxin, IL-5, IL-12(p40) and VEGF. While there were no significant differences at baseline, exercise mice had significantly lower IL-5 and VEGF compared to control at the 20 week time point. Nexrutine also significantly reduced circulating IL-9 concentrations. No significant differences were observed when compared to the control group. Immunohistochemistry of tumor sections showed significantly lower expression of pAkt in Nexrutine fed mice with no visible differences for NFκB. In conclusion, both Nexrutine and exercise suppressed tumor growth. Though similar outcomes were seen in this comparative effectiveness study, the mechanisms by which exercise and Nexrutine exert this benefit may focus on different pathways.